RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY AKIBAT PERLAKUAN UREA DAN PUPUK KANDANG KAMBING - Bondar, Benito; Sirait, Bilter; Manurung, Agnes Imelda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
The aim of this research was to determine the response of oil palm seedlings in pre nursery to Urea and Goat Manure treatment. This research used a factorial Randomized Block Design consisting of the first factor, Urea treatment with 3 levels, namely: U0 = 0 g/polybag, U1 = 3 g/polybag and U2 = 6 g/polybag. The second factor is the dose of Goat Manure (K) with 3 treatment levels, namely: K1 = 0 g/polybag, K2 = 200 g/polybag and K3 = 400 g/polybag. The results showed that fertilization with urea 6 g/polybag significantly increased plant height, stem diameter, number of leaves, leaf length, leaf width and leaf area. Treatment with a dose of Goat Manure at a dose of 400 g/polybag significantly increased the growth of plant height, stem diameter, number of leaves, leaf length, leaf width and leaf area. The combination between Urea and the dose of Goat Manure has a significant effect on plant height, stem diameter, number of leaves, leaf length, leaf width and leaf area.